Blood eosinophil levels as a biomarker in COPD. (May 2018) - Brusselle, Guy; Pavord, Ian D.; Landis, Sarah; Pascoe, Steven; Lettis, Sally; Morjaria, Nikhil; Barnes, Neil; Hilton, Emma
Abstract: Chronic obstructive pulmonary disease (COPD) is a heterogeneous disorder and patients respond differently to treatment. Blood eosinophils are a potential biomarker to stratify patient subsets for COPD therapy. We reviewed the value of blood eosinophils in predicting exacerbation risk and response to corticosteroid treatment in the available literature (PubMed articles in English; keywords: "COPD" and "eosinophil"; published prior to May 2017). Overall, clinical data suggest that in patients with a history of COPD exacerbations, a higher blood eosinophil count predicts an increased risk of future exacerbations and is associated with improved response to treatment with inhaled corticosteroids (in combination with long-acting bronchodilator[s]). Blood eosinophils are therefore a promising biomarker for phenotyping patients with COPD, although prospective studies are needed to assess blood eosinophils as a biomarker of corticosteroid response for this. Highlights: Blood eosinophils are a promising biomarker in COPD. Increased blood eosinophils without ICS therapy predict increased exacerbation risk. Increasing blood eosinophils counts predict improved response to ICS. Prospective studies are needed to confirm use of blood eosinophils as biomarkers and precise implications in clinical care.